Solar Energy Project, Activities Junior High Science - Department of Energy, Washington, DC.; Tullock, Bruce; Department of Energy, Washington, DC.; New York State Education Dept., Albany. Bureau of Science Education; State Univ. of New York, Albany. Atmospheric Science Research Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
This guide contains lesson plans and outlines of science activities which present concepts of solar energy in the context of the junior high science curriculum. Each unit presents an introduction; objectives; skills and knowledge needed; materials; methods; questions; recommendations for further work; and a teacher information sheet. The teacher information sheet presents the target grade levels; the areas of science involved in the lesson; background information; hints on gathering materials; suggested time allotment; suggested approach; typical results; precautions; modifications; and evaluation. (RE)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 (Stock Number 061-000-00228-6; $2.75).
ERIC Note: For related documents, see SE 028 406-413.
Educational level discussed: Junior High Schools.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Class Activities; Energy; Environmental Education; Junior High Schools; Lesson Plans; Science Curriculum; Science Education; Science Experiments; Secondary Education; Solar Radiation; Technological Advancement; Technology; Energy Education; Guides, Classroom -- Teacher